BER estimation for STBC-MC-DS-CDMA-4 antennas system by varied wavelet-carriers features via AWGN-flat channels - Khadam, Nader Abdullah; Kadhim Jawad Alrubaie, Ali Jawad; Jumah Al-Thahab, Osama Qasim (Institute of Advanced Engineering and Science, 2024)
This paper improves the bit error rate (BER) of the modern communication system by taking into account the effect of the wavelet shape and the number of carriers on the performance of the space time block code multi-carrier direct sequence code division multiple access (STBC-MC-DS-CDMA). Here the transmitter is moved with speeds 2 km/hr, 45 km/hr and 100 km/hr via Rayleigh flat fading channel. Here, 2 antennas are employed at the receiver to mitigate the multipath signal influence. The system’s orthogonal frequencies are generated using Haar, Daubechies 4, Symlets 4, Cohen-Daubechies-Feauveau 1.1 with 9.7 and B-spline 3. The number of used carriers is 128, 512, and 1,024. Quadrature phase shift key (QPSK) is used with cyclic prefix 1/16 and a bandwidth of 20 MHz. traditional fast fourier transform (FFT) system is compared to the proposed discrete wavelet packet transform (DWPT) to show the BER enhancements. The space-time block coding (STBC) is used to enhance system cabability in error corection. The proposed system shows significant improvement in BER, so that, it reaches to the same BER when using FFT but with less signal to noise ratio (SNR), which interns reduce the power consumed within the system and the cost.